(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
The article talks about the importance of strategic competence in teaching students of future teachers of pre-conscription military training. Strategic competence as one of the significant characteristics of students of future teachers of pre-conscription initial training for successful intercultural communicative activity